2003
DOI: 10.1196/annals.1304.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harmane on the Convulsive Threshold in Epilepsy Models in Mice

Abstract: The study investigated the activity of harmane on maximal electroshock seizures (MES) and seizures induced by pentilentetrazole (PTZ) in mice. Initial studies established convulsive current 50 (CC(50)) values or MES and effective dose 50 (ED(50)) for PTZ to produce seizures. Harmane (2.5, 5.0, or 10 mg/kg intraperitoneally) increased the threshold of seizures in MES dose-dependently. The convulsions produced by PTZ were decreased by the low dose of harmane (2.5 mg/kg), but the high dose of harmane (10 mg/kg) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Previous reports have shown that intraperitoneal injection of harmine suppresses bone resorption in vivo 12 , but also induces significant neurotoxic effects 13 - 15 . To minimize the undesired side effects, harmine was prepared into oil-in-water oral emulsion for our in vivo study.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous reports have shown that intraperitoneal injection of harmine suppresses bone resorption in vivo 12 , but also induces significant neurotoxic effects 13 - 15 . To minimize the undesired side effects, harmine was prepared into oil-in-water oral emulsion for our in vivo study.…”
Section: Resultsmentioning
confidence: 96%
“…Intraperitoneal administration with harmine was able to suppress OVX-induced bone loss in mice 12 . However, it should be noted that intraperitoneal injection of harmine could cause serious central nervous system side effects 13 - 15 , 26 , which impede the development of harmine toward wider clinical applications 26 . In this study, we generated an oil-in-water harmine emulsion and found that the oral administration of harmine in emulsion form reduced harmine accumulation in the mouse brain.…”
Section: Discussionmentioning
confidence: 99%
“…Harmine is a harmala alkaloid (Figure 5A) and generally these alkaloids have a wide spectrum of pharmacological actions, including MAO inhibition, binding to benzodiazepine receptors, convulsive or anticonvulsive actions and tremorogenesis (Aricioglu et al, 2003; Glennon et al, 2000; Guan et al, 2001; Husbands et al, 2001; Kim et al, 1997; Lutes et al, 1988; Song et al, 2004). To gain some insight into the specificity of harmine’s ability to up-regulate glutamate transporter gene expression, we tested the activities of anumber of harmine analogs.…”
Section: Resultsmentioning
confidence: 99%
“…It is also present in common plant-derived foods and in human tissues (Guan et al, 2001). Known pharmacologic effects of harmine include hallucinogenesis (Sourkes, 1999), convulsive or anticonvulsive actions (Aricioglu et al, 2003), and tremor (Guan et al, 2001; Lutes et al, 1988). Several potential molecular targets for these central pharmacologic effects of harmine have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…However, the side effects, like neurotoxicity had also been noted for many years. Accumulating evidences indicated that harmine was also a tumorigenic agent, and can induce convulsion and Straub tail in mouse model (Ahmed et al, 1959;Saano et al, 1982;Aricioglu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%